Cicero’s artes liberales and the Liberal Arts - Tempest, Kathryn (Ciceroniana On Line, 2020)
This article examines Cicero’s concept of the artes liberales within his larger vision for education. Starting with the codification of a curriculum in the work of Martianus Capella, it explores the reception of Cicero’s works in the early development of the canon before turning back to the contexts of Cicero’s original thinking on the subjects. In particular, it illustrates how Cicero sought to broaden the curriculum and make the artes relevant for life in first-century BC Rome, combining traditional Greek learning with innovative topics on modern history and political science. In so doing I suggest some of the ways in which Cicero’s arguments on the value of a broad education still echo in our ideas of the Liberal Arts today before ending with some reflections on the political context in which they were produced.